A new tool available for hydrogeologists: the Airborne EM method - Viezzoli, Andrea; Menghini, Antonio (Acque Sotterranee - Italian Journal of Groundwater, 2014)
The Airborne EM method has nowadays reached a great degree of progress, so that it can be considered a reliable tool for the hydrogeological modeling. It is indeed able to provide a detailed distribution of resistivity, so that it is possible to draw information of stratigraphic and, sometimes, of hydrochemical type. But, in order to achieve this outcome, it is demanded a high performance of the instrumentations, as such as an accurate data processing. We show some examples of application of the AEM method, for the solution of problems connected to the groundwater mapping, to the seawater intrusion and to the improvement of the hydrogeological models.